Viking Vik and the wolves - Rayner, Shoo (London : Orchard, 2009)
Viking Vik is guarding the goats in the hills when he sees Greeneyes the Wolf. Wulf laughs at Vik. Everyone knows Greeneyes isn't real! But Wulf stops laughing when he hears a howl in the night
Keywords: Adventure stories